Pengenalan Object Theatre pada remaja Bremi Lombok Timur - Riyana Rizki Yuliatin; Puspita Dewi; Baiq Desi Dwi Arianti; Hary Murcahyanto (Universitas Hamzanwadi, 2021)
The theatre is one of the performing arts fields that display human behavior on stage. Human life is represented through stories, dialogues, and the behavior of the characters. One of the styles in theatre art is object theatre. Object theatre involves manipulating objects to give life to the objects used so that there is a reciprocal play between the player and the object. Object theatre itself is still relatively new in Indonesia, aiming to introduce object theatre to the public. The target of this activity is Bermi Youth, Pancor Village aged 17-20 years. Teenagers can become a faster medium for disseminating information to the next generation. The activity was held for four months with a total of 14 participants. The training methods used in this activity are workshops, training assistance, and performances at the Pengadangan Village hall, which was the earthquake's location in 2018. The activity results showed that the trainees were able to stage object theatre performances and control themselves during the show by not stealing the show.